2023
DOI: 10.1002/smll.202206026
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated MINFLUX Nanoscopy, through Spontaneously Fast‐Blinking Fluorophores

Abstract: The introduction of MINFLUX nanoscopy allows single molecules to be localized with one nanometer precision in as little as one millisecond. However, current applications have so far focused on increasing this precision by optimizing photon collection, rather than minimizing the localization time. Concurrently, commonly used fluorescent switches are specifically designed for stochastic methods (e.g., STORM), optimized for a high photon yield and rather long on‐times (tens of milliseconds). Here, accelerated MIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 69 publications
0
15
0
1
Order By: Relevance
“…[50] Tuning the equilibrium into the blinking range can be also be achieved by substitution of the 3carboxylic acid with an ortho-trifluoroethylamide, which led to HaloTag-compatible self-blinking analogs of 500R and TMR, [42] or with substituted lactams resulting in dye ligands compatible with MINFLUX imaging. [51] Intermolecular reactions can also lead to blinking behaviors, as was observed for pyronines undergoing reversible nucleophilic addition of glutathione. The corresponding HaloTag ligands were applicable in living cells, using only endogenous glutathione.…”
Section: Photoactivatable Photoswitchable and Blinking Fluorophore Li...mentioning
confidence: 94%
See 1 more Smart Citation
“…[50] Tuning the equilibrium into the blinking range can be also be achieved by substitution of the 3carboxylic acid with an ortho-trifluoroethylamide, which led to HaloTag-compatible self-blinking analogs of 500R and TMR, [42] or with substituted lactams resulting in dye ligands compatible with MINFLUX imaging. [51] Intermolecular reactions can also lead to blinking behaviors, as was observed for pyronines undergoing reversible nucleophilic addition of glutathione. The corresponding HaloTag ligands were applicable in living cells, using only endogenous glutathione.…”
Section: Photoactivatable Photoswitchable and Blinking Fluorophore Li...mentioning
confidence: 94%
“…However, attaching the ligand to the 5‐position minimized this protein interaction and enabled SMLM of tubulin in live cells (Figure 5a). [50] Tuning the equilibrium into the blinking range can be also be achieved by substitution of the 3‐carboxylic acid with an ortho ‐trifluoroethylamide, which led to HaloTag‐compatible self‐blinking analogs of 500R and TMR, [42] or with substituted lactams resulting in dye ligands compatible with MINFLUX imaging [51] . Intermolecular reactions can also lead to blinking behaviors, as was observed for pyronines undergoing reversible nucleophilic addition of glutathione.…”
Section: Functional Fluorophore Ligandsmentioning
confidence: 99%
“…However, we found that such constructs suffered from poor reactivity of the Tz moiety and were susceptible to hydrolytic cleavage of the Tz unit. In our second strategy, we constructed a PaX (S9, see Supporting Information) with an acrylate moiety as the linker/radical trap, which served to generate a series of the dyads bearing either secondary (9,10) or tertiary (11,12) acrylamide linkages. Initial TD-DFT studies 28 anticipated excited state energy transfer to the Tz moiety in both the singlet and triplet manifolds for the PaX structures, regardless of linkage (Figure S1a), as well as quenching of the singlet excited state of the photogenerated (i.e., "closed-form") pyronine fluorophore (PaX CF , Figure 1b and Figure S1b).…”
Section: Synthesis and Characterization Of Pax Tetrazinementioning
confidence: 99%
“…To prepare the acrylamide-linked PaX scaffolds (9−12), new acrylate-functionalized PaX were prepared (S9, see Supporting Information for details) and coupled to commercially available tetrazine amines to yield the secondary acrylamide products (9,10). To access the tertiary Nmethylacrylamides (11,12), N-methyl-4-(6-methyl-1,2,4,5tetrazin-3-yl)benzylamine 41 was additionally synthesized and coupled with the acrylic acids S9 and S14 (see Supporting Information). Much to our surprise, the acrylamide-derived PaX scaffolds showed notably slower photoactivation rates, likely due to the greater electron deficiency of the radical trap.…”
Section: Synthesis and Characterization Of Pax Tetrazinementioning
confidence: 99%
See 1 more Smart Citation